Microencapsulation of nutmeg essential oil (Myristica fragrans) via spray drying: effects of feed emulsion parameters on emulsion and powder characteristics - Ana Kemala Putri Jauhari; Jou Gerry Septian Riseno; Hidrotunnisa Hidrotunnisa (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2022)
Nutmeg essential oil (Myristica fragrans) is susceptible to deterioration and chemically unstable when exposed to the environment, resulting in a loss of bioactive compounds and the development of off-flavors. Microencapsulation is then used to enhance shelf stability and nutritional value. This study aimed to attempt the nutmeg essential oil encapsulation, utilizing the spray drying technique by analyzing the effect of emulsion parameters. An array of process parameters including wall material content (7, 8, and 9%), the mass ratio of carrageenan to soy protein isolate (1:2, 1:1, 2:1), and concentration of essential oil (25, 50, and 75%) were thoroughly investigated. The results showed that almost all parameters significantly influence (p < 0.05) on determining emulsion and powder quality. The microencapsulation process with a mass ratio of carrageenan to soy protein isolate of 1:2 gave better microcapsules characteristics than other powders. The microencapsulation process that was performed with a solid content of 7% as wall material and nutmeg essential oil at the concentration of 25% as core material showed the best performance, resulting in the highest solid yield (83.33±0.37%) with good emulsion characteristics (i.e. stability, viscosity, and diameter droplet) and powder properties (i.e. moisture content, total solid, hygroscopicity,  and color).